Residents’ support for sustainable cultural heritage tourism development in Sarawak: perceived tourism benefits perspective and quality of life as mediating / Ida Ingko - Ingko, Ida (2022)
The tourism industry brings in economic, environmental, and socio-cultural benefits which contribute to the revitalization of the local communities and improve local communities’ standard of life. Thus, to achieve successful sustainable tourism development, community leaders and developers need to view tourism as a ‘community industry’ as this enables local communities to actively decide and plan future tourism development. This study emphasized the quality of life (QOL) as a mediation factor in examining its relationship with residents of Kuching's perceived tourism benefits and their support towards sustainable tourism development (SSTD). This study adopted a quantitative approach via online questionnaires to Kuching residents. A total sample size of 200 was selected using the purposive sampling technique. PLS-SEM was performed using SmartPLS 3.3 to analyze the data. The result shows that perceived tourism benefits do influence residents’ perspectives on QOL and residents' SSTD. However, the empirical result shows that QOL is not significant on SSTD. Results on the mediating impact of QOL on the relationship between perceived tourism benefits and SSTD are also revealed in this study. Furthermore, adding on political trust to the dimensions of perceived tourism benefits which originally only tested economic, social, cultural, and environment into residents’ support in cultural heritage tourism development having varying levels and magnitude of impacts on local communities. The research suggested that the government must ensure the outcomes of tourism benefits must continue to be seen and witnessed by the residents in impacted cultural heritage tourism areas. It is hoped that the study can contribute to the successful sustainable cultural heritage tourism development in Kuching, Sarawak.